AAV Vectors Containing rDNA Homology Display Increased Chromosomal Integration and Transgene Persistence - Wang, Zhongya (Nature Publishing Group, 2012)
Although recombinant adeno-associated viral (rAAV) vectors are promising tools for gene therapy of genetic disorders, they remain mostly episomal and hence are lost during cell replication. For this reason, rAAV vectors capable of chromosomal integration would be desirable. Ribosomal DNA (rDNA) repeat sequences are overrepresented during random integration of rAAV. We therefore sought to enhance AAV integration frequency by including 28S rDNA homology arms into our vector design. A vector containing ~1 kb of homology on each side of a cDNA expression cassette for human fumarylacetoacetate hydrolase (FAH) was constructed. rAAV of serotypes 2 and 8 were injected into Fah-deficient mice, a model for human tyrosinemia type 1. Integrated FAH transgenes are positively selected in this model and rDNA-containing AAV vectors had a ~30× higher integration frequency than controls. Integration by homologous recombination (HR) into the 28S rDNA locus was seen in multiple tissues. Furthermore, rDNA-containing AAV vectors for human factor IX (hFIX) demonstrated increased transgene persistence after liver regeneration. We conclude that rDNA containing AAV vectors may be superior to conventional vector design for the treatment of genetic diseases, especially those associated with increased hepatocyte replication.